Production of bioethanol from carrot discards - Aimaretti, Nora Rosa (2012)
A revalorization of discarded carrots as substrate for the production of second-generation ethanol is proposed. In order to increase the fermentable sugar concentration of the musts two strategies were studied: Strategy 1 consisted in the enzymatic hydrolysis of bagasse must and Strategy 2 by which carrots were milled, dropped into distilled water and hydrolyzed with different enzymes prior to compressing and filtering to obtain carrot must. By applying Strategy 2 using 0.05% (v/v) of the enzyme Optimase CX255 at 70 C and pH 5.5 during 2.5 h, the fermentable sugars extracted increased 3.5 times. In this way, the production of 77.5 L of ethanol for each ton of discarded carrots was achieved. This process yielded bagasse as byproduct, which could be used for animal feed.